1998
DOI: 10.1098/rspb.1998.0465
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet cues affect the foraging behaviour of blue tits

Abstract: The function of avian ultraviolet (UV) vision is only just beginning to be understood. One plausible hypothesis is that UV vision enhances the foraging ability of birds. To test this, we carried out behavioural experiments using wild-caught blue tits foraging for cabbage moth and winter moth caterpillars on natural and arti¢cial backgrounds. The light environment in our experiments was manipulated using either UVblocking or UV-transmitting ¢lters. We found that the blue tits tended to ¢nd the ¢rst prey item (o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(85 citation statements)
references
References 39 publications
2
83
0
Order By: Relevance
“…However, there is also experimental evidence that UV cues are important for foraging and motion detection in birds, which show a preference for UVreflecting targets such as fruits (Church et al, 1998;Siitari et al, 1999;Rubene et al, 2010;Werner et al, 2012). Therefore, for a common prey of birds that are potentially capable of UV vision, it would be advantageous to possess a colour pattern that also provides camouflage in this spectral region, especially in open environments where UV radiation is available (Endler, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is also experimental evidence that UV cues are important for foraging and motion detection in birds, which show a preference for UVreflecting targets such as fruits (Church et al, 1998;Siitari et al, 1999;Rubene et al, 2010;Werner et al, 2012). Therefore, for a common prey of birds that are potentially capable of UV vision, it would be advantageous to possess a colour pattern that also provides camouflage in this spectral region, especially in open environments where UV radiation is available (Endler, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous studies investigated the use of UV reflectance for avian detection of mammalian prey [9], insect prey [10], and mature fruit [11]. Beyond the detection and recognition of food items [12,13], UV cues may also provide birds with information regarding the quality of foods [e.g., quality or ripeness of fruit; 1,14].…”
Section: T R a C T A R T I C L E I N F Omentioning
confidence: 99%
“…As a plumage or integument characteristic, UV reflectance may signal male fitness in terms of resource acquisition or overall health [13] and [14]. Behavioral studies also have demonstrated the potential importance of UV reflectance for foraging activities in frugivores [15] and insectivores [16].…”
Section: Introductionmentioning
confidence: 99%